The legality of drone strikes under international humanitarian law - Magwaza, Wayne (Department of Public Law, 2025)
The increasing use of armed drones in armed conflict presents significant questions as to the legality of their use under International Humanitarian Law. There has been a protracted debate amongst scholars on this subject. As the use of drones becomes more prevalent, it has become more important to examine whether their use in armed conflict does not violate some existing rules of International law. The analysis of whether or not drone strikes violate international law has been debated in terms of two regimes of law; jus in bello which applies during armed conflict and jus ad bellum which refers to the conditions under which states may resort to the use of force. The present research is focused on the use of drones in armed conflict and therefore pays attention to the jus in bello aspect in determining the permissibility of drone strikes during armed conflict. This thesis seeks to explore specific rules of International Humanitarian Law (IHL) and determine whether drone strikes are capable of conforming to these principles. The thesis highlights the historical, current and most likely future use of drones and discusses the implications of such use under IHL. In that regard, the research utilises examples of contemporary conflict situations in which drones have been employed. The lack of transparency and accountability with regard to drone strikes has also provoked a considerable amount of debate in the media and amongst international law scholars. Thus, the thesis seeks to further highlight the issues pertaining to liability in case of alleged violations and suggests how this should be dealt with.